Platelet-derived growth factor activity and mRNA expression in healing vascular grafts in baboons. Association in vivo of platelet-derived growth factor mRNA and protein with cellular proliferation. - Golden, M A (1991)
In a baboon graft model of arterial intimal thickening, smooth muscle cells (SMC) have been observed to proliferate underneath an intact monolayer of endothelium and in the absence of platelet adherence. Because platelets are not present and therefore cannot be a major source of growth stimulus, we have proposed that the vascular wall cells in the graft intima express mitogens and regulate SMC proliferation. To test this hypothesis, we assayed the grafts for mitogenic activity and expression of growth factor genes. Segments of healing graft and of normal artery, when perfused ex vivo, released mitogenic activity into the perfusate. The graft released more mitogen than the normal arterial segment, and some of the activity was inhibitable with an antibody to human platelet-derived growth factor (PDGF). In addition, Northern analysis of total RNA demonstrated higher expression of PDGF-A chain mRNA in the graft intima compared to normal artery. PDGF-B chain mRNA was barely detectable in both tissues. PDGF mRNA levels within the graft interstices were not measured. In situ hybridization of 7.5- or 12-wk grafts indicated that some luminal endothelial cells and adjacent intimal SMC contained PDGF-A chain mRNA. By thymidine autoradiography, intimal SMC were observed to be proliferating in the inner third of the intima. These data demonstrate a difference in the pattern of PDGF transcript expression and luminal perfusate activity in graft as compared with control arteries. The association of intimal smooth muscle cell proliferation with intimal PDGF mRNA expression and release of PDGF-like protein supports the hypothesis that factors from cells that have grown into the graft or populated its surface rather than platelets may regulate intimal smooth muscle cell proliferation in this model.